2010
DOI: 10.1186/1471-244x-10-70
|View full text |Cite
|
Sign up to set email alerts
|

Borna disease virus (BDV) circulating immunocomplex positivity in addicted patients in the Czech Republic: a prospective cohort analysis

Abstract: BackgroundBorna disease virus (BDV) is an RNA virus belonging to the family Bornaviridae. Borna disease virus is a neurotropic virus that causes changes in mood, behaviour and cognition. BDV causes persistent infection of the central nervous system. Immune changes lead to activation of infection. Alcohol and drug dependence are associated with immune impairment.MethodsWe examined the seropositivity of BDV circulating immunocomplexes (CIC) in patients with alcohol and drug dependence and healthy individuals (bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The study not only confirmed the existence of BDV infection in Lithuania but interestingly found that the CIC prevalence in healthy Lithuanians ranged at the lowest level of 22.4 % so far reported from Europe, differing particularly from the high level of 37 % in another Eastern European country [40]. The result of one-fifth of healthy carriers did, however, support the concept that BDV is a moderate pathogen with a majority of sub-clinical infections [37].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The study not only confirmed the existence of BDV infection in Lithuania but interestingly found that the CIC prevalence in healthy Lithuanians ranged at the lowest level of 22.4 % so far reported from Europe, differing particularly from the high level of 37 % in another Eastern European country [40]. The result of one-fifth of healthy carriers did, however, support the concept that BDV is a moderate pathogen with a majority of sub-clinical infections [37].…”
Section: Discussionmentioning
confidence: 57%
“…Except the Czech Republic [40], no information on BDV prevalence exists in East European countries with regard of these sensitive test systems. How BDV infection is determined and whether or not the most sensitive systems are applied is of paradigmatic significance, because pathogenicity is reversely associated with infection prevalence of the pathogen [37].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of depressive symptoms correlated with the concentration and duration of antigenaemia (Bode et al, 2001). In study reported by Rackova and colleagues, a significantly higher rate of BDV CIC positivity was found in psychiatric patients with a more severe psychopathology than in patients with a milder symptomatology, as measured by psychiatric scales (Rackova et al, 2009). …”
Section: Bdv Positivity and Psychopathologymentioning
confidence: 84%
“…Only one study detected BDV positivity in addicted patients at the start of detoxification and at the end of treatment. Rackova and colleagues demonstrated BDV CIC positivity in 36.6% and 42.9% of patients with alcohol and drug abuse; the positivity of BDV infection was not significantly higher than in healthy individuals (Rackova et al, 2010). The rate of BDV positivity ranged from negative results to positivity in 42.9% (see Table 3).…”
Section: Borna Disease Virus Infection and Addictionmentioning
confidence: 95%
See 1 more Smart Citation